HOST PROTEASE INHIBITION BY SPECIFIC PATHOGENS IN PERIODONTAL DISEASE - S, Saipriya; Chava, Vijay Kumar (International Journal of Research -GRANTHAALAYAH, 2018)
Proteolytic tissue degradation is a typical phenomenon in chronic inflammatory periodontal disease with the uncontrolled release of host and bacterial derived proteases causing self-digestion and tissue destruction. Antimicrobial proteins and peptides constitute a diverse class of host defense molecules that act early to combat invasion and infection with bacteria and other microorganisms and protease inhibitors forms one of the functional classes of antimicrobial peptides. Plasma protease inhibitors present in gingival crevicular fluid as well as tissues may play a critical role in the protection of periodontal tissues by modulating protease activity, more particularly during active phases. This literature review attempts to highlight the role of host protease inhibitors and their interaction with specific periodontal pathogens in the pathogenesis of periodontal disease.